Comparative Evaluation of Date Palm Types (Phoenix dactylifera L.) under the Conditions of the Northern State, Sudan (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was accomplished to assess the comparativeperformance of the dry, semi-dry and soft date palm types under theconditions of the Northern State, Sudan. Four date representativecultivars, grown in Elghaba Agricultural Scheme, were compared;.theirage ranged between 30 and 34 years. The cultivars were Barakawi andGondaila (dry), Wadkhteeb (semi-dry) and Madina (soft). Data recordedfor vegetative growth parameters were stem circumference, leaf numberand length, number of pinnae/leaf, length of pinnae, number of thorns/leafand width of leaf base. Data were also collected for number of bunches,bunch weight and yield/palm. The results indicated significant differencesbetween the four cultivars. Wadkhteeb excelled the other cultivars innumber of leaves, bunch weight and yield/palm, without being affected bythe phenomenon of alternate bearing. The superiority of Wadkhteeb inyield is indicative of the suitability of the semi-dry cultivars to theconditions of the Northern State.
Keywords: Date palm; cultivars; adaptation; vegetative growth; yield